(untitled) (International Journal of Engineering and Computer Science, 2017)
The resource management is the main problem in the cloud. Anchor used for fetching stable matching policies when mapping the virtual machine’s to physical servers and clients and the operators are mapping virtual machine’s to physical servers based on the preferences of the user request. In the proposed system, Anchor is the many to one stable matching with heterogeneous resources needs to server. The system used in the large-scale resources management system based on the workload traces. To realize with diverse set of policy goals with good performance. In the system bandwidth estimation algorithm to estimate the data bandwidth of the particular uploading data and the downloading data in the various cloud resources. In the every cloud server’s offer services different from other resources. So, the virtual node can formed and enhance the services and rectify the network based resources problems and give the optimal solutions to the various cloud based resources. The cloud can scaled among different resources and give the effective services in the cloud environment